Evaluer la performance économique, le bien-être et la soutenabilité. Rapport du Conseil d'analyse économique et du Conseil allemand des experts en économie - Conseil d'Analyse Économique; Sachverständigenrat zur Begutachtung der gesamtwirtschaftlichen Entwicklung (La Documentation Française, 2010)
– The Franco-German Ministerial Council decided on February 4, 2010 to ask the French Conseil d'Analyse Économique (CAE) and the German Council of Economic Experts (GCEE) to follow-up on the outcome of the “Commission on the Measurement of Economic Performance and Social Progress” (Stiglitz-Sen-Fitoussi Commission, or SSFC). The corresponding report of the CAE and GCEE discusses how comprehensiveness and accuracy of an indicator set might be traded off optimally with parsimony and cost to provide a reliable basis for regular, timely and digestible reporting on three key issues regarding economic performance, quality of life and sustainability.
Keywords: 330